Communication Concientization of Inclusion Education in Palu - Ni Nyoman Suhermi; Muh. Nur Ali; Achmad Herman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aim of this is to uncover and analyze the responses of relevant stakeholders regarding the implementation of inclusive education in Palu City; participatory communication models regarding the implementation of inclusive education in Palu City through a concentrated perspective; and exploring the embodiment of a participatory communication model in the implementation of inclusive education in Palu City which involves related stakeholders. This study uses naturalistic research methods because of the research is carried out in natural setting. Data collection technique was carried out through observation, interviews, documentation, and FGD. The data analysis technique includes four stages, namely: data collection, data reduction, data presentation, and drawing conclusions or data verification. The results of this study indicate that: (1) The stakeholders involved in participatory communication provided suggestions regarding efforts which related to the implementation of inclusive education in Palu City; (2) The model of conscientization communication for the implementation of inclusive education in Palu City must involve various stakeholders consisting of local governments, schools, parents, NGOs, and local mass media; (3) The realization of the participatory communication model regarding the implementation of inclusive education in Palu City based on the involvement and participation of stakeholders which refers to their real participation in educational activities. Limitations and suggestions for further research are revealed in this study.